PHP & MySQL Web Development All-in-One Desk Reference For Dummies - Valade, Janet (Wiley Publishing, 2011)
If you want to build dynamic Web sites that encourage users to interact with them, PHP and MySQL are among the best tools you’ll find. PHP is a scripting language designed specifically for use on the Web, while MySQL is a database management system that works with it perfectly. Best of all, they’re free. It’s hard to beat that combination!